Automatized Parameterization of the Density‐functional Tight‐binding Method. II. Two‐center Integrals. Issue 1 (7th September 2015) - Witek, Henryk A.; Chou, Chien‐Pin; Mazur, Grzegorz; Nishimura, Yoshifumi; Irle, Stephan; Aradi, Bálint; Frauenheim, Thomas; Morokuma, Keiji
Abstract: We present an efficient numerical integration scheme (TWOCENT) to be used in the context of automatized parameterization of the density‐functional tight‐binding (DFTB) method. The accuracy of the integration process is assessed and its range of applicability is discussed. The functionality of the developed code is tested by reproducing the electronic portion of the existing mio parameter sets and by reproducing a series of reference DFT band structures of elemental solids. Abstract : We present an efficient numerical integration scheme to be used in the context of automatized parameterization of the DFTB method. The functionality of the developed code is tested by reproducing the electronic portion of the existing parameter sets and a series of reference DFT band structures of elemental solids.